STRATEGY ANALYSIS TO IMPROVE SERVICE QUALITY IN INDIHOME PRODUCTS ON CUSTOMER SATISFACTION AT TELKOM WITEL MEDAN - Sri Kartika Dewi; Nuri Aslami (Transpublika Publisher, 2022)
This study aims to analyze PT Telkom Witel Medan's strategy for improving the quality of service on IndiHome products in order to increase customer satisfaction. This study employs a qualitative descriptive research methodology. Consequently, observation and interviews were employed to collect data for this study. This investigation was carried out at PT Telkom Witel Medan. The findings of the study revealed that the strategy for improving the quality of service on IndiHome products in order to increase customer satisfaction is already very effective and is getting better every month, as the MyIndiHome application makes it very simple for customers to obtain product-related information, suggestions, and complaints. In addition to providing services in accordance with the Standard Operating Procedure (SOP), Telkom Witel Medan employs various strategies to ensure customer satisfaction and brand loyalty. Telkom Witel Medan uses two ways of measuring IndiHome customer satisfaction: a complaint and suggestion system and a customer satisfaction survey system, such as distributing questionnaires to customers regarding service quality and customer satisfaction with IndiHome products.